2020
DOI: 10.1111/1750-3841.15479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat flour particle size on physicochemical properties and quality of noodles

Abstract: The effect of particle size on the physicochemical and noodle quality of wheat flours was investigated. Granular wheat flour was ground by adjusting the distance between the rolls (0.02, 0.04, 0.06, 0.08, and 0.1 mm) of the flour mill to obtain wheat flour in five different particle sizes. The results showed that milling intensity significantly reduced the particle size and increased the damaged starch content and sedimentation value, but there were no significant differences in protein or ash contents.The red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These results were contributed to by the stronger gel network structure due to the fine particle size and moderate starch damage. Some studies [ 36 , 37 ] have suggested that, to a certain extent, the finer the particles, the better the textural parameters such as hardness and elasticity of the noodles, which was conducive to improving the consumer acceptability of products.…”
Section: Resultsmentioning
confidence: 99%
“…These results were contributed to by the stronger gel network structure due to the fine particle size and moderate starch damage. Some studies [ 36 , 37 ] have suggested that, to a certain extent, the finer the particles, the better the textural parameters such as hardness and elasticity of the noodles, which was conducive to improving the consumer acceptability of products.…”
Section: Resultsmentioning
confidence: 99%
“…(1994) discovered the negative relationship between the granule size of starches and hardness of noodles, and Guan et al . (2020) indicated that the adhesiveness was higher in the noodles made from wheat flour with smaller particle sizes. However, the granule size of pea starch was comparatively larger, and the hardness of PN was also higher in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding chewiness, it was significantly lower in the extruded group than the nonextruded group but not significantly different from the high‐gluten group. Higher chewiness was related to a greater content of damaged starch (Guan et al, 2020), suggesting that the taste of stewing noodles with extruded wheat bran was similar to that of stewing noodles made with high‐gluten flour.…”
Section: Resultsmentioning
confidence: 99%